A Child’s Right to Education: What Can the International Community Do? - Lahiri, Sajal (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2019)
Children from poor families often do not go to school and work as wage labourers instead. This perpetuates their poverty status. How does one break this vicious circle? This article discusses different options that the international community can consider and the shortcomings of some of the policies that it has been pursuing. The article argues that carrots are more likely to work than sticks, and one has to look at other areas such as the availability of credits in order for educational policies to be more effective.